PENGARUH PENGETAHUAN INVESTASI, PERSEPSI RISIKO, DAN PERSEPSI KONTROL PERILAKU TERHADAP MINAT INVESTASI SAHAM - Fahreza, Muhammad; Surip, Ngadino (SWOT : Jurnal Ilmiah Ilmu Manajemen, 2019)
In 2016, the Indonesia Stock Exchange as the organizer of stock investments in Indonesia for 10 consecutive years had a quite high rate of return compared to the major exchanges in the world. However, judging from the number of Indonesian local citizen who use this investment, their numbers are still in the low category. Therefore, researchers are interested in examining the factors that influence the Indonesian stock investment intention. After presurvey, there are three variables that occupy the highest rank and also become the reason for respondents to not or have not invest in stocks, namely investment knowledge, risk perception, and perceived behavioral control. The research data is collected through. The population in this study are all people who have never invested shares, independent income, and located in the area of Jakarta. The sampling method used is the Roscoe method with the number of members of the sample at least ten times the number of variables studied. The number of respondents used in this study was 100 respondents. The results showed that the investment knowledge affect the stock investment intention, the perceived risk affect the stock investment intention, the perceived behavioral control affect the stock investment intention, and the investment knowledge, perceived risk, perceived behavioral control affect the stock investment intention simultaneously.